Metabolic Bone Disorders Are Predictors for 2-year Adverse Outcomes in Patients Undergoing 2–3 Level Anterior Cervical Discectomy and Fusion for Cervical Radiculopathy or Myelopathy. Issue 3 (3rd April 2023) - Diebo, Bassel G.; Kovoor, Matthew; Alsoof, Daniel; Beyer, George A.; Rompala, Alexander; Balmaceno-Criss, Mariah; Mai, David H.; Segreto, Frank A.; Shah, Neil V.; Lafage, Renaud; Passias, Peter G.; Aaron, Roy K.; et al.
Abstract : Study Design: Retrospective cohort study utilizing the New York statewide planning and research cooperative system. Study Objective: To investigate postoperative complications of patients with metabolic bone disorders (MBDs) who undergo 2–3 levels of anterior cervical discectomy and fusion (ACDF). Summary of Background Data: MBDs and cervical degenerative pathologies, including cervical radiculopathy (CR) and cervical myelopathy (CM), are prevalent in the aging population. Complications with ACDF procedures can lead to increased hospitalization times, more expensive overhead, and worse patient outcomes. Method: Patients with CM/CR who underwent an ACDF of 2–3 vertebrae from 2009 to 2011 with a minimum 2-year follow-up were identified. Patients diagnosed with 1 or more MBD at baseline were compared with a control cohort without any MBD diagnosis. Cohorts were compared for demographics, hospital-related parameters, and 2-year medical, surgical, and overall complications. Binary multivariate logistic regression was used to identify independent predictors. Results: A total of 22, 276 patients were identified (MBD: 214; no-MBD: 22, 062). Among MBD patients, the majority had vitamin D deficiency (n = 194, 90.7%). MBD patients were older (53.0 vs 49.7 y, P < 0.001), and with higher Deyo index (1.0 vs 0.5, P < 0.001). MBD patients had higher rates of medical complications, including anemia (6.1% vs 2.3%), pneumonia (4.7% vs 2.1%), hematoma (3.3% vs 0.7%), infection (2.8% vs 0.9%), and sepsis (3.7% vs 0.9%), as well as overall medical complications (23.8% vs 9.6%) (all, P ≤0.033). MBD patients also experienced higher surgical complications, including implant-related (5.7% vs 1.9%), wound infection (4.2% vs 1.2%), and wound disruption (0.9% vs 0.2%), and overall surgical complications (9.8% vs 3.2%) (all, P ≤0.039). Regression analysis revealed that a baseline diagnosis of MBD was independently associated with an increased risk of 2-year surgical complications (odds ratio = 2.10, P < 0.001) and medical complications (odds ratio = 1.84, P = 0.001). Conclusions: MBD as a comorbidity was associated with an increased risk of 2-year postoperative complications after 2–3 level ACDF for CR or CM.